Religious Extremism in Nigeria: Boko Haram as Case Study - Muhammad Asif (Journal of Political Studies, 2019)
The world observed the transformation process of Continent Africa from Colonialism to independence with hopes and fears. In Cold War Era, the African states have been engaged by the superpowers, on strategic and economic fronts, with certain limitations. On the other hand, in Post-Cold War phase, the Continent Africa had been addressed with laudable objectives. Now, the wave of religious extremism, in Continent Africa, has been perceived as a serious security threat, compelled to the international community to pay serious attention to deal the African states. There is no doubt that the entire region has multidimensional challenges and opportunities and its picture has to be drawn at larger canvass. The objective of the present research paper is to analyze those factors, which given space to Boko Haram, a religious extremist organization, in Nigeria. No exaggeration in saying Boko Haram extremely disturbed the internal and external dynamic of the state. Now, it has become a burden on the political and economic life of Nigeria. The qualitative research methodology has been used to argue the issue of religious militancy in Nigeria, in the context of Boko Haram. Secondary source of data has been used by keeping in mind the theoretical nature of the research paper. The study determines that the military operations are not sole solution to counter the religious extremism of Boko Haram until the economic, social and political issues of the Nigerian society are not addressed. There is a dire need to establish strong commitment level of the common Nigerian over the political system otherwise the issue of Boko Haram will remain intact.